Immunodistribution of RFamide-related peptide-3 (RFRP-3) during the seminiferous epithelium cycle in a desert rodent Psammomys obesus. (April 2021) - Djouahra, Nassima; Moudilou, Elara N.; Exbrayat, Jean-Marie; Hammouche, Sadjia
Highlights: The seminiferous epithelium cycle in Psammomys obesus comprises 14 stages. RFRP-3 is expressed in Sertoli, Leydig and germ cells. RFRP-3 highly abundant in late pachytene spermatocytes I at stages XI and XII seems involved in meiotic divisions. Abstract: The Sand rat, Psammomys obesus, living northwest of the Algerian Sahara, presents a seasonal reproductive cycle. The purposes of this study were firstly to determine the stages of seminiferous epithelium cycle (SEC) by histological and morphometric analysis and secondly to investigate, for the first time, the testicular expression of RFamide-related peptide-3 (RFRP-3) during the SEC by immunohistochemistry. The results showed that the SEC consists of 14 stages according to the tubular morphology method. RFRP-3 was observed in both testicular compartments: the tubular and the interstitial. Leydig cells exhibited the highest RFRP-3 signal (30.73 % ± 4.80) compared to Sertoli cells (13–15 %). In the germline, RFRP-3 was detected during the late prophase I of meiosis in late pachytene, diplotene and metaphasic spermatocytes I. In addition, only round and triangular spermatids were positive during spermiogenesis. Referring to the SEC, it was found that the increased staining of RFRP-3 in spermatocytes I coincided with late pachytene of XI and XII stages (16.90 % ± 0.69 and 16.61 % ± 0.28, respectively). In spermatids, the labeling decreased in the triangular ones at stage IX (8.04 % ± 0.42). These results suggest the involvement of RFRP-3 in the control of SEC in P. obesus .